Recanalization treatment for acute ischemic stroke: 3-month outcome before and after implementation of routine endovascular treatment - Kati Valkonen; Nicolas Martinez-Majander; Gerli Sibolt; Marjaana Tiainen; Silja Räty; Tatu Kokkonen; Kimmo Lappalainen; Sami Curtze (eNeurologicalSci, 2022)
Background and purpose: Endovascular treatment for acute ischemic stroke has become a recommended treatment option for selected patients after several randomized controlled trials have shown the effectiveness of endovascular treatment. Due to the nature of randomized clinical trials, the generalizability to population based real life settings and the resulting benefits remain difficult to estimate. Methods: We included 896 consecutive patients treated with intravenous thrombolysis (IVT) within 4.5 h of stroke onset between January 2016 and December 2018, who were treated with additional endovascular treatment according to the new evidence when indicated (new-IVT-cohort). This cohort was compared to 913 intravenous thrombolysis patients treated in the 4.5 h time-window between January 2011 and December 2013 before the era of endovascular treatment (old-IVT-cohort). Results: In the new-IVT-cohort there were 253 intravenous thrombolysis + endovascular treatment treated patients. The new-IVT-cohort was associated with a better outcome on the modified Rankin Scale at 3 months in univariable ordinal regression (OR 1.27; 95% CI 1.08–1.49). The association remained significant (OR 1.65; 95% CI 1.27–2.14) also after adjustment for following confounding factors: sex, NIHSS, diabetes, atrial fibrillation, hypertension, coronary artery disease, hypercholesterolemia, myocardial infarction, heart failure, history of ischemic stroke, history of TIA, and use of antithrombotic, statins, antihypertensive, anticoagulation treatment, or endovascular treatment (Fig. 1). Conclusion: We were able to verify the efficacy of endovascular treatment in a real life cohort of intravenous thrombolysis patients even when only 28% of the patients are eligible for endovascular treatment on top of intravenous thrombolysis treatment.